Five new species and three new records of burmeistera (campanulaceae-lobelioideae) from colombia (2012)
Five new species of Colombian Burmeistera are described and illustrated and theirrelationships with other species from Colombia, Central America, Venezuela, andEcuador are discussed. Three of the newly described species are from the WesternCordillera, one from the Central Cordillera and one is restricted to the northern partof the Eastern Cordillera. Along with the descriptions of these new species, we recordthe presence of B. formosa, B. smaragdi, and B. venezuelensis for the first time inColombia. Some guidelines to collect Burmeistera specimens are also included topreserve distinctive traits that are often lost once they have been pressed and dried